Cost Model of Activity Oriented Municipal Solid Waste Management: Integration of Activity Based Costing/Management and Causal Loop Diagram - Dermawan, Dedi; Mulyadi, Agus; Wardana, Sajidi (Universitas Ahmad Dahlan, 2025)
The increasing generation of municipal solid waste (MSW) in Pekanbaru, a densely populated city in Riau Province, has led to higher waste management costs. In 2023, the city generated 1,011 tons of waste daily, with management costs reaching around IDR 93 billion. Traditional cost calculation methods are often inaccurate, failing to account for the activities involved in MSW management. This study develops an activity-based cost management model using Activity-Based Costing/Management (ABC/M) to map costs to specific waste management activities, combined with Causal Loop Diagrams (CLD) to analyze activity relationships and formulate a mathematical cost model. The application of ABC/M identified four primary waste management activities: collection, transportation, processing, and disposal. The results show a total waste management cost of approximately IDR 91 billion, with CLD revealing dynamics such as the impact of incentives on recycling rates and the balancing effects of transportation and waste bank usage on waste generation. This study contributes provides a novel cost model for municipal waste management, offering both theoretical and practical contributions for improving cost efficiency and resource allocation.